Literature Study: International Monetary System and the Threat of Recession - Adelina Fransiska Sianturi; Azhar Suganda; Yeremi Siagian (Outline Publisher, 2024)
This study was conducted to gather sufficient information on the relationship between the International Monetary System and the threat of recession. The method used in this study is through a literature study that collects previous research in answering the relationship and role of the International Monetary System with the threat of recession. The IMF and World Bank estimate that the world economy will experience a recession which is also accompanied by an increase in the rate of inflation in 2022 and 2023. Big countries in the world economy such as Europe, the USA, China and India are also expected to experience economic recession and high inflation. Interestingly, the ASEAN 5 region (including Indonesia) will actually experience positive economic growth with a moderate rate of inflation. Based on the results of this literature, it can be concluded that an economic recession can threaten the world economy, especially in the field of the international monetary system.